2012
DOI: 10.1111/j.1365-2966.2012.21479.x
|View full text |Cite
|
Sign up to set email alerts
|

Jet-induced star formation in gas-rich galaxies

Abstract: This article has been accepted for publication in Monthly Notices of the Royal Astronomical Society. ?? 2012 The Author(s). Published by Oxford University Press on behalf of the Royal Astronomical Society. All rights reserved. The version of record is available online at doi:10.1111/j.1365-2966.2012.21479.x.Feedback from active galactic nuclei (AGN) has become a major component in simulations of galaxy evolution, in particular for massive galaxies. AGN jets have been shown to provide a large amount of energy a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
267
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 244 publications
(310 citation statements)
references
References 99 publications
41
267
0
2
Order By: Relevance
“…This excess corresponds to about a factor of two. A similar increase in SFR due to the onset of radio jets has been suggested also by simulations of massive, gas-rich, high-redshift galaxies (Silk & Nusser 2010;Gaibler et al 2012).…”
Section: The Dependence Of Star Formation On Radio Jetssupporting
confidence: 79%
See 1 more Smart Citation
“…This excess corresponds to about a factor of two. A similar increase in SFR due to the onset of radio jets has been suggested also by simulations of massive, gas-rich, high-redshift galaxies (Silk & Nusser 2010;Gaibler et al 2012).…”
Section: The Dependence Of Star Formation On Radio Jetssupporting
confidence: 79%
“…van Breugel et al 2004;Gaibler et al 2012;Wagner et al 2012;Ishibashi & Fabian 2012). Simulations have shown that, although powerful jets' interaction with the ISM might be volume limited, the resulting pressure can impact the galactic disk also at larger radii and eventually all of the galaxy (see Gaibler et al 2012). Thermal or kinetic AGN feedback is often thought to heat and expel most residual gas from the galaxy (e.g.…”
Section: The Dependence Of Star Formation On Radio Jetsmentioning
confidence: 99%
“…Bower et al 2006;Werner et al 2013;Chen et al 2013b). However, a positive radio mode feedback has also been suggested (Silk & Nusser 2010;Kalfountzou et al 2012Kalfountzou et al , 2014Gaibler et al 2012). In this scenario, the radio jets drive shocks in the interstellar medium which enhance the star formation, something that has been observed for decades now (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…Right: Image of jet interacting with cold gas disc and a hot ambient medium. See Gaibler et al (2012) for details of the jet modeling. resolution) with orbital parameters that can be considered 'average' for a LCDM cosmology.…”
Section: Figure 2 Left(2 Panels)mentioning
confidence: 99%
“…Jets could potentially keep the hot halo hot, preventing 16 L. C. Powell et al it from being a fuel supply. We are currently testing simulations which combine idealised merger simulations including hot gas haloes with the jet module presented in Gaibler et al (2012) (see Fig. 2,, in order to address this issue.…”
Section: Star Formation Fueled By Hot Gas Haloes In Mergersmentioning
confidence: 99%